Spatiotemporal Dynamics of Land Surface Temperature and Its Impact on the Vegetation - Ghulam Shabir Solangi; Altaf Ali Siyal; Pirah Siyal (Salehan Institute of Higher Education, 2019)
Due to global warming under climate change scenarios, Indus delta region of Pakistan is under serious threat since the last few decades. The present study was thus conducted to determine the spatiotemporal variations in the LST and its impact on the vegetation of the Indus delta, using satellite data for the past 27 years (1990-2017). The analysis revealed that on average, there was an increase of 1.74 oC in LST during the last 27 years. The temporal variation in the Normalized Difference Vegetation Index (NDVI), an indicator of vegetation, showed the highest NDVI of 0.725 in the year 2005 followed by the year 2010 with NDVI of 0.712. While the lowest NDVI of 0.545 was observed during the year 2017. The LST was integrated with NDVI which showed a fair but negative statistical correlation with a coefficient of determination R2 = 0.65. A correlation analysis between NDVI and the yield of the wheat crop of the Delta showed a positive relationship with R2 = 0.89. Several factors may contribute to an increase in LST, such as an increase in residential areas, change in the cropping pattern and overall global climate change. Such studies are important for determining the climatic influences on ecological parameters.